On the Interests of Non-human Animals in Traditional Yorùbá Culture: A Critique of Ọ̀rúnmìlà - Ofuasia, Emmanuel (Bangladesh Journal of Bioethics, 2018)
Traditional Yorùbá culture admits the hegemonic locus that humans rank above all else on the planet. The outlook received decisive ratification several millennia ago in one of the Odùs of their Ifá Corpus. Specifically, in Odù Ògúndá Otura, one of the numerous chapters of the Ifá Corpus, Ọ̀rúnmìlà, the founder and primordial deity of Ifá discloses his authorization, the use of non-human animals for sacrifice and other human ends interminably. In this study, we engage the Ifá chapter that upholds this outlook. We riposte that the age long supercilious perspective among the Yorùbá that humans rank higher and over non-human animals, as documented in the said Odù is no longer tenable on biological and moral-legal grounds. If the biological and moral-legal thrusts are not invalid, what framework is plausible when the interest(s) of non-human animals clash with the interest(s) of Ifá tradition and Yorùbá culture? On what basis will it be appropriate to jettison the interest(s) of the one for the interest(s) of the other? In the light of these posers, we employ Kai Horsthemke’s ethical individualism as the suitable groundwork that considers the interest of animals recommended for sacrifice in Ifá obeisance.